EVALUATION OF ASSOCIATION BETWEEN BONE MINERAL DENSITY AND VASCULAR CALCIFICATION IN CHRONIC KIDNEY DISEASE PATIENTS - SAEED , AA; KHALID , P; ABBAS , G; KAUSAR , SAZ; SHAN , M; KHAN , S (Biological and Clinical Sciences Research Journal, 2023)
A one-year prospective study was conducted in the Nephrology Department of Nishtar Hospital, Multan, to analyze the association between bone mineral density and vascular calcification in patients with chronic kidney disease. The study included 80 patients at various stages of chronic kidney disease. Vascular calcification was calculated using echocardiography, the Kauppila score, and the ankle-brachial index. Bone mineral density was computed by using total body densitometry. The study results showed that 41.25% of the patients (33 patients) had a Kauppila score more significant than one. Peripheral vascular calcification was observed in 22.5% of the patients (18), whereas 40% (36) had valvular calcification. Moreover, ABI and heart lesions were found to be positively correlated. The study also revealed that bone mineral density was an independent determinant, and valvular calcification was significantly associated with the total BMD and BMD of the femoral neck and femur. Therefore, the study concluded that there is a significant correlation between vascular calcification and bone mineral density in patients with chronic kidney disease.